MOBILE-BASED REGIONAL SONG APPLICATION USING THE FLUTTER FRAMEWORK - Maftoha, Bayu; Oktavira, Rina (Jurnal TAM (Technology Acceptance Model), 2024)
The background of this research is children who have difficulty learning folk songs, only by being facilitated by books containing song lyrics makes children often forget the tone of the song being sung. Regional songs are a form of culture that have distinctive characteristics that distinguish one region from another both in terms of language, instruments and the values contained in the song itself[1]. Folk songs are one of the arts that must be preserved by children. Based on this problem, the researcher created a mobile-based folk song application using the Flutter framework to make it easier to learn and keep abreast of developments in an era that depends on technology.